Exploring the Role of TikTok in Enhancing English Learning Motivation among Indonesian Students - Eby Delyani Sitompul; Deasy Yunita (Faculty of Education and Teacher Training of UIN Palopo, 2025)
This research investigates the impact of TikTok on junior high school students' English learning motivation and identifies effective content types. Using a descriptive qualitative approach with supporting quantitative data, this study involved 7 students from SMPN 2 Pandan Nauli who regularly engaged with English learning content on TikTok. Data was collected through questionnaires, semi-structured interviews, and content observation. The findings show that students feel more motivated to learn English through TikTok content, especially vocabulary tips, idiomatic expressions, and pronunciation, which are presented in an interesting, easy-to-understand, and contextually appropriate way. While TikTok cannot replace formal education, its effectiveness as a complementary learning tool depends on the quality of the content and students' ability to integrate it into their learning routines. This study recommends that educators utilize digital platforms like TikTok to foster a more engaging, flexible and meaningful English learning experience for today's generation.